2005
DOI: 10.1158/1078-0432.ccr-04-1848
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Profile of Colorectal Cancer: Identification of Markers of Prognosis

Abstract: Purpose: The cytochromes P450 (P450) are a multigene family of enzymes with a central role in the oxidative metabolism of a wide range of xenobiotics, including anticancer drugs, carcinogens, and endogenous compounds. The purpose of this study was to define the P450 profile of colorectal cancer and establish the prognostic significance of expression of individual P450s in colorectal cancer. Experimental Design: Immunohistochemistry for a panel of 23 P450s was done on a colorectal cancer tissue microarray consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 44 publications
12
143
1
3
Order By: Relevance
“…Although a variety of endogenous hormones or signaling factors have been suspected to favor metastasis (Aguirre-Ghiso, 2007), little is known in this field on the effects of pollutants. Three independent studies examined cytochrome P450 profile expression in different metastatic tumors and found a significant upregulation of some AhR-target members, including CYP1B1, CYP2S1 and aromatase CYP19 (Downie et al, 2005;Kumarakulasingham et al, 2005;Haas et al, 2006), which is in line with our hypothesis. However, the mechanisms of these upregulations remain elusive particularly because other cytochrome P450 genes are also increased.…”
Section: Discussionsupporting
confidence: 86%
“…Although a variety of endogenous hormones or signaling factors have been suspected to favor metastasis (Aguirre-Ghiso, 2007), little is known in this field on the effects of pollutants. Three independent studies examined cytochrome P450 profile expression in different metastatic tumors and found a significant upregulation of some AhR-target members, including CYP1B1, CYP2S1 and aromatase CYP19 (Downie et al, 2005;Kumarakulasingham et al, 2005;Haas et al, 2006), which is in line with our hypothesis. However, the mechanisms of these upregulations remain elusive particularly because other cytochrome P450 genes are also increased.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a blast search was used to determine that the peptide was unique to annexin A4 (SVLAYRNTA corresponding to amino acids 39 -47 of annexin A4), thus ensuring no crossreactivity with other proteins. The annexin IV peptide conjugated to ovalbumin was used to immunise rabbits subsequently followed with four boosters, with a protocol we have previously used for the development of other antibodies (Kumarakulasingham et al, 2005). Nine weeks after the initial booster, rabbits were bled and serum was tested by ELISA using the peptide as an immunogen.…”
Section: Antibodiesmentioning
confidence: 99%
“…Permission for this study was obtained from the Grampian Research Ethics Committee. A colorectal cancer tissue microarray was constructed as described Kumarakulasingham et al, 2005). The tumours within the array were representative of the distribution of anatomical locations and the Dukes stages found in colorectal cancers within this population.…”
Section: Tumour Samples and Tissue Microarray Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type COX and LOX pathway genes elicit the most potent inflammatory signalling molecules; therefore, blocking these pathways show additive effect in colon cancer cells 65 . We detected mutations in CYPC219 gene, which is known to overexpress in hepatocellular carcinoma in Chinese patients 66 , and also in CYP2U1 gene, which is overexpressed in colorectal and ovarian cancers 67,68 . Combined target inhibition of various combinations of COX, LOX, CYP enzymes as well as inhibition of AA metabolites are effective in human oesophageal, colon, breast and skin cancer 1 .…”
Section: Number Of Somatic Mutationsmentioning
confidence: 97%